L’èthos : un articulateur - Dominique Maingueneau (Contextes)
From the 1980’s onwards, èthos became established in the field of literary studies and in the meantime it functions – so to speak – as one of the field’s key-concepts. However, as it appears from the unregulated manner in which ‘èthos’ interferes with concepts such as ‘posture’, ‘style’ and ‘authorial scenography’, its meaning still remains to be defined. In this article, I first point out that this instability existed from the very beginning, in Aristotle’s work, and that the ‘èthos’ concept authorizes various interpretations, depending on the specific conceptualization and on the corpus. Thus, I personally conceptualized ‘èthos’ based on the idea of ‘incorporation’, which turned out to be extremely productive when studying specific text types, such as advertising, political or legal texts. In a second part of my article, I touch upon some difficulties raising to the surface when the concept is applied to literary texts, where ‘èthos’ is often defined rather vaguely and where the analyzed corpus’ distinctive features are never fully taken into consideration. I illustrate this idea by means of three examples, taken from three different genres and three different centuries: Molière’s Les précieuses ridicules, the incipit in Voltaire’s Candide and a sonnet by José-Maria de Hérédia. This will lead to the observation that no analysis of ‘èthos’ can be carried out without taking into account the historical background, the genre and the aesthetic positioning of the text.